Hybridité ou Dissonance ? Quelques réflexions épistémologiques et méthodologiques sur la réception du Festival du Film Tunisien à Paris - Patricia Caillé (Mise au Point)
Moroccan, Algerian and Tunisian cinemas have distinct histories, approaches, aesthetics and economies. Nevertheless, the films from these countries that arrive in France and/or Europe (only a small fraction of the national productions) tend to be gathered together under larger regional categories such as Maghrebi or Arab cinema. This article focuses first on the number and circulation of the films coming to France from each of these countries in order to examine the terms of the relationship between « Maghrebi cinema » and « national cinema ». Second, using the results of a questionnaire, it focuses on the reception of the small Tunisian Film Festival that took place in Paris in 2008 in order to understand who these spectators are. I analyse their motivations, how they construct their relationship to such an event and to the films that are shown, and the film cultures that underlie such reflections.